A Comparative Study of Head‐Mounted and Table‐Mounted Augmented Vision Systems for Assembly Error Detection. Issue 1 (24th April 2012) - Odenthal, Barbara; Mayer, Marcel Ph.; Kabuß, Wolfgang; Schlick, Christopher M.
Abstract Within the Cluster of Excellence "Integrative Production Technology for High‐Wage Countries, " a research project has been initiated to study self‐optimizing assembly cells and to design innovative ergonomic human–machine interfaces of the cell's numerical control. An experimental assembly cell was designed in which two robots carry out a certain repertoire of coordinated pick‐and‐place operations with small workpieces. To support the human operator while monitoring the operations and intervening in the case of assembly errors, an Augmented Vision System (AVS) has been designed and developed. The study described in this article deals with the ergonomic presentation of assembly information by the AVS to support the human operator in detecting assembly errors in small workpieces. Two laboratory experiments were carried out to compare two visual display types and to investigate different variations of presenting assembly information. Forty‐eight subjects participated in the experiments. The statistical analysis shows that the use of a head‐mounted display instead of a common table‐mounted display for the AVS increases the accuracy of assembly error detection significantly (α = 0.05). In contrast, a trend toward a longer detection time was found. © 2012 Wiley Periodicals, Inc.